The Amelioration of Post Tin Mining Sand Tailing Medium with Chicken Manure for Pepper Cultivation - Ismed Inonu; Riwan Kusmiadi; Ayu Yuliana; Eddy Nurtjahya (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2020)
Inonu I, Kusmiadi R, Yuliana A, Nurtjahya E. 2020. The amelioration of post tin mining sand tailing medium with chicken manure for pepper cultivation. Jurnal Lahan Suboptimal: Journal of Suboptimal LandsÂ 9(1): 31-40.Â Pepper cultivation in tin mining sand tailings requires the amelioration of organic matter to improve soil characteristics. The paper investigates the effect of chicken manure dosage on the growth of three pepper cultivars in sand tailing medium. This study was conducted on April-August 2016 at Experiment Station of Universitas Bangka Belitung, Balunijuk Village, Bangka Island. This study was arranged in a completely randomized design with two factors and three replications. The first factor was the dosage of chicken manure (5 kg; 6 kg; 7 kg/plant). The second factor was pepper cultivars (Lampung Daun Lebar; Lampung Daun Kecil; Merapin). The. result of the analysis of variance showed that the treatment of chicken manure dosage significantly affected only on total leaf area. The treatment of pepper cultivars significantly affected the total of chlorophyll, root dry weight, and shoot dry weight. There was no interaction between chicken manure dosage and pepper cultivar. Pepper cv. Lampung Daun Lebar tends to grow better than the other cultivars in the sand tailing medium.